Individual heterogeneity and effects of harvest on greater sage‐grouse populations. Issue 5 (16th April 2017) - Caudill, Danny; Guttery, Michael R.; Terhune, Theron M.; Martin, James A.; Caudill, Gretchen; Dahlgren, David K.; Messmer, Terry A.
ABSTRACT: The influence of harvest on wild populations has been the focus of substantial debate, and has widespread implications for the management of wild populations. Traditional views of harvest are based on density‐dependent responses of populations to harvest. However, alternate mechanisms can and do induce compensation (e.g., individual heterogeneity). Selective harvest of successful females and their offspring is thought to occur in some grouse populations (e.g., blue grouse [ Dendragapus spp.], greater sage‐grouse [ Centrocercus urophasianus ]), and delaying harvest within a season has been proposed as a viable strategy to overcome this type of selective harvest. However, a recent examination regarding the effects of harvest on greater sage‐grouse strongly criticized the recommendation of delayed harvest. Herein, we address the criticism of the delayed harvest strategy and provide an examination of projecting the effects of harvest in the face of individual heterogeneity using deterministic projection models. We demonstrate that under proportional harvesting strategies, given a fixed harvest rate, early additive harvest does not have a larger effect on the population than additive harvest later in the season. Moreover, we show that when higher quality individuals (i.e., individuals with higher survival and reproductive rates) are more susceptible to harvest, individual heterogeneity in harvest effects will induce depensatory dynamics when density‐dependent effects are only additive. Conversely, even when density‐dependent effects are additive, if lower quality individuals are more susceptible to harvest, heterogeneity will induce partial compensation. Reducing the selectivity of harvest on higher quality individuals (i.e., shifting harvest onto lower quality groups) could reduce the risk of artificial selection and induce partial compensation. Therefore, we recommend managers consider the spatiotemporal patterns of populations and time harvest to maximize the heterogeneity tradeoff between higher and lower quality individuals. © 2017 The Wildlife Society. Abstract : Individual heterogeneity could play an important role in the effects of harvesting free‐ranging animals. Managers should consider spatiotemporal patterns in wild populations, which will aid in optimizing harvest strategies.